The Role of Social Media as Intervening Variable on Purchase Through Motivation - Kapriani Kapriani; Ikhsan Amar Jusman (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
The role of social media is currently very important in motivating consumers to purchase products, especially in the fashion industry. The purpose of this study was to determine the role of social media on purchasing decisions through motivation at D'fashion Textile & Tailor. The sample used in this study was 97 respondents with a probability sampling technique. Source data were obtained through a questionnaire. The data analysis used is partial least squares (PLS). The results of the study show that social media has an effect on purchasing decisions and motivation. In addition, motivation also influences purchasing decisions.